Translate semiotics? Tools for transdisciplinarity - Demaria, Cristina (E|C, 2020)
With the background knowledge acquired in many years of research within fields of studies whose objects are similar to those analysed by semiotics, the article tries to lists the possible theoretical - as well as ethical and political - questions that may allow us both to specify a semiotic perspective, and to open up this perspective to an effective transdisciplinary dialogue. Leaving definitive or allencompassing answers aside, in the first part the paper tries to clarify what is meant by “transdisciplinary gaze”, and which are its main categories, along with their heuristic potential. In the second part of the article, the ways in which semiotics can offer to other fields of research not only a method intended as an organon, but also tools to face contemporary “problems” and issues, are discussed. This direction of research may be useful to develop further the political and ethical sides of a transdisciplinary research that finds in its application, and in the continuous perfecting of its method, the way to be a therapeutic of the social body.